Islam and the limits of the state : reconfigurations of practice, community and authority in contemporary Aceh - Feener, R. Michael; Kloos, David; Samuels, Annemarie (Leiden studies in Islam and society ;, 2016)
This book examines the relationship between the state implementation of Sharia and diverse lived realities of everyday Islam in contemporary Aceh, Indonesia. With chapters covering topics ranging from NGOs and diaspora politics to female ulama and punk rockers, the volume opens new perspectives on the complexity of Muslim discourse and practice in a society that has experienced tremendous changes since the 2004 Indian Ocean tsunami. These detailed accounts of and critical reflections on how different groups in Acehnese society negotiate their experiences and understandings of Islam highlight the complexity of the ways in which the state is both a formative and a limited force with regard to religious and social transformation.